2009
DOI: 10.3354/meps07916
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the connectivity between sea scallop populations in the Middle Atlantic Bight and over Georges Bank

Abstract: The dispersion and settlement of sea scallop larvae spawned on Georges Bank (GB) and in the Great Southern Channel (GSC) were explored using an individual-based population dynamics model. The model consisted of 4 pelagic life stages (egg, trochophore, veliger, and pediveliger) and 3 benthic life stages (juvenile, young adult, and adult). It was driven by the 1995 to 2005 hindcast flow field predicted by the Finite Volume Coastal Ocean Model (FVCOM) in the Gulf of Maine (GOM), with spawning stocks specified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…The diversity of habitats used by species, and effects of habitat variation on vital rates, including movements, determine the productivity, stability and resilience of regional populations (Secor et al 2009, Tian et al 2009, Kerr et al 2010. Furthermore, the effects of habitat diversity and its loss on the resilience and stability of populations that serve as ecosystem keystones should be translated across a level of ecological organization to affect ecosystem productivity, resilience, and stability.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…The diversity of habitats used by species, and effects of habitat variation on vital rates, including movements, determine the productivity, stability and resilience of regional populations (Secor et al 2009, Tian et al 2009, Kerr et al 2010. Furthermore, the effects of habitat diversity and its loss on the resilience and stability of populations that serve as ecosystem keystones should be translated across a level of ecological organization to affect ecosystem productivity, resilience, and stability.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Both the intensity and direction of physical processes naturally vary in time, and changes to the environmental properties that regulate species distributions are likely to impact these processes as well. Churchill et al (2011) demonstrated that the retention of cod larvae on the New England coast is substantially impacted by the presence of upwelling vs. downwelling regimes, and Tian et al (2009b) related the retention of Georges Bank scallop larvae to the strength of the tidal mixing front. Further analysis of the robustness of our results to variability in these processes and other forcing properties would be highly informative, and may be possible using available forcing data.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative is to assign each particle a probability of settling during each timestep, then remove it from further consideration after settlement (e.g. Tian et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Particle counts in particle-tracking studies vary widely from a few thousand (e.g., Huret et al 2007;Tian et al 2009a) to tens of millions (e.g., Watson et al 2012;Jones et al 2015). Field research that relies on parentage, tagging, or drifter data may be limited to only a few hundred sample points (Almany et al 2007;Planes et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Each particle may only contribute to one destination, which excludes settlement criteria based on the proportion of time that a particle spends within a destination region (e.g., Huret et al 2007). An alternative is to assign each particle a probability of settling during each time step and then remove it from further consideration after settlement (e.g., Tian et al 2009b).…”
Section: Discussionmentioning
confidence: 99%